CoOx / SnO2 hydrogen-sensitive material as well as preparation method and application thereof

Through the preparation method of CoOx/SnO2 hydrogen-sensitive material, the composite interface between CoOx and SnO2 is used to improve hydrogen sensitivity and response speed, and solve the problems of high working temperature, high cost and low sensitivity of existing hydrogen-sensitive materials, achieving safety and Improved economy.

CN119125242APending Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411263494.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing hydrogen-sensitive materials can easily cause safety accidents due to excessive working temperature, which is high cost and low sensitivity.

Method used

Using the preparation method of CoOx/SnO2 hydrogen-sensitive material, the heterostructure and adjustable phase composition are prepared by mixing cobalt source and Sn2+-containing alkaline aqueous solution, adding urea reagent, ultraviolet sonication, drying and heat treatment processes. The CoOx/SnO2 hydrogen-sensitive material uses the composite interface of CoOx and SnO2 to improve the adsorption and catalytic properties of the material.

Benefits of technology

It effectively reduces the working temperature of the material, improves the sensitivity and response speed to hydrogen, reduces production costs, and realizes the controllability of the material composition and simplicity of operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125242A_ABST
    Figure CN119125242A_ABST
Patent Text Reader

Abstract

The invention discloses a CoOx / SnO2 hydrogen-sensitive material as well as a preparation method and application thereof, and belongs to the technical field of heterogeneous composite materials. Firstly, a tin source and a cobalt source are mixed to prepare a uniform solution, the pH value of the solution is adjusted to be alkaline, urea is added to adjust the existence form of cobalt ions, the solution serves as a morphology control agent of the material, the obtained mixed solution is subjected to ultraviolet ultrasonic treatment, aging, drying, grinding and heat treatment processes, and the target sensitive material is obtained. The material is large in specific surface area, adjustable in cobalt ion valence and high in oxygen defect distribution density, has the outstanding advantages of low working temperature, high sensitivity, good hydrogen selectivity and the like, and is particularly suitable for being applied to high-sensitivity, low-power-consumption and safe detection sensors required by hydrogen detection. The invention solves the technical problems that the existing hydrogen-sensitive material is easy to cause safety accidents due to too high working temperature, and the cost is high and the sensitivity is low due to the adoption of noble metal raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heterogeneous composite materials and particularly relates to a CoO x / SnO2 hydrogen sensitive material and its preparation method and application. Background Art

[0002] Hydrogen is abundant in nature, has a high calorific value, and its combustion products are non-polluting to the environment. It is a new type of clean energy. Hydrogen is colorless and odorless. A small amount of hydrogen mixed with oxygen can burn or even explode. Therefore, hydrogen-sensitive detection plays an extremely important role in safe production.

[0003] Tin dioxide (SnO2) is a wide-bandgap n-type semiconductor material that exhibits excellent performance in the fields of light detection, solar cells, catalysis, and gas-sensitive detection, and has broad application prospects. As a semiconductor gas-sensitive material, tin dioxide has the advantages of high sensitivity, fast response, and good stability, and is currently recognized as one of the best gas-sensitive semiconductor materials. However, in practical applications, SnO2 gas sensors still have some disadvantages, such as poor selectivity and high operating temperature, which is extremely unfavorable for hydrogen sensitive detection, because hydrogen is extremely easy to burn or even explode in a high-temperature environment, increasing the unsafety of operation.

[0004] In addition, patent CN114609198A discloses a tin oxide-based hydrogen sensing material based on rare earth element doping and precious metal modification, and its preparation method and application. It uses precious metals such as gold (Au) in chloroauric acid solution, platinum (Pt) in platinum chloride solution, palladium (Pd) in chloropalladic acid solution, and silver (Ag) in silver nitrate solution as sensitive catalysts, which greatly increases the cost of hydrogen sensitive materials. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a CoO x / SnO2 hydrogen-sensitive material and its preparation method and application are used to solve the technical problems of existing hydrogen-sensitive materials that are prone to safety accidents due to excessively high working temperature, high cost due to the use of precious metal raw materials, and low sensitivity.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A kind of CoO x / SnO2 hydrogen sensitive material preparation method, the steps are as follows:

[0008] 1) Cobalt source solution and Sn-containing 2+ The alkaline aqueous solution is fully mixed to form a mixed solution, wherein the cobalt source and Sn 2+ The molar ratio is 1:(0.2-5.0);

[0009] 2) adding urea reagent to the mixed solution to obtain a precursor solution;

[0010] 3) subjecting the precursor solution to ultraviolet ultrasonic treatment, aging, drying and grinding to obtain powder;

[0011] 4) Heat treat the powder to obtain the target product CoO x / SnO2 hydrogen sensitive material.

[0012] Preferably, containing Sn 2+ The alkaline aqueous solution was prepared by dissolving analytically pure SnCl2·2H2O in deionized water to control the concentration of [Sn 2 + ]=(0.5-5.0)mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 5-12, and stir evenly to obtain the product.

[0013] Preferably, the cobalt source solution is prepared by dissolving analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water, the molar ratio of the two salts is 1:(0.2-5.0), and the cobalt ion concentration in the solution reaches (0.5-6.0) mmol·L -1 .

[0014] Preferably, in step (2), the mass fraction of the urea reagent in the mixed solution is 0.1%-4.5%.

[0015] Preferably, the above-mentioned ultraviolet ultrasonic treatment uses a mercury lamp, the ultrasonic power is 50W-300W, and the treatment time is 0.5h-4h; after the ultraviolet ultrasonic treatment, the precursor solution needs to be aged at room temperature for 12h and placed in a 60°C oven to be fully dried.

[0016] Preferably, the conditions of the heat treatment process are: placing the obtained powder in a muffle furnace, heating it to 300°C-600°C at a rate of 2°C / min-20°C / min, keeping it warm for 1-5h, then cooling it to 100°C at a rate of 10°C / min, and finally cooling it with the furnace to obtain the target product.

[0017] A method using the above-mentioned CoO x CoO / SnO2 hydrogen sensitive material preparation method x / SnO2 hydrogen-sensitive material, which has a heterogeneous structure and adjustable phase composition.

[0018] Preferably, the hydrogen sensitive material is used in detecting hydrogen.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention discloses a CoO x Preparation method of / SnO2 hydrogen sensitive material. First, cobalt source and Sn containing 2+ The alkaline aqueous solution is mixed in a certain proportion, wherein Sn 2+ The hydrolysis and oxidation in alkaline aqueous solution have a moderate hydrolysis rate, and the macromolecules generated by the reaction with cobalt salts have an appropriate coordination number when subjected to heat treatment, resulting in a cobalt oxide compound with an adjustable composition. Secondly, the addition of urea can, on the one hand, adjust the existence form of cobalt ions and serve as a morphology control agent for the material; on the other hand, the use of urea can regulate the cobalt source and Sn-containing 2+ The degree of hydrolysis of the metal salt in the mixed solution of the alkaline aqueous solution; thirdly, since urea has a weak reducing effect under solvent conditions, it reacts with the cobalt source solution to make the Sn-containing 2+ The tin-containing complex ions in the alkaline aqueous solution form bonds with the cobalt source, and after nucleation, growth, and crystallization, combined with the regulation of ultraviolet ultrasound technology, aging, drying, grinding and heat treatment processes, the material composition can be controlled to obtain the target product CoO with a specific particle size, morphology and distribution. x / SnO2 hydrogen sensitive material.

[0021] Furthermore, the present invention uses stannous chloride as the tin source and a mixture of cobalt nitrate and cobalt chloride as the cobalt source as raw materials. These raw materials are relatively easy to obtain and have low costs, which is conducive to reducing the overall production cost. x There are many active gas adsorption sites at the composite interface with SnO2, which can regulate the adsorption of the material. There is also CoO at the composite interface that can catalyze hydrogen-sensitive reactions. x , which can improve the sensitivity of hydrogen-sensitive materials. At the same time, the energy band at the composite interface is bent, and the separation and conduction efficiency of carriers are changed, thereby regulating the semiconductor responsiveness of the material. The method of the present invention effectively improves the adsorption and sensitivity of the material to the target gas molecules, reduces the activation energy of the material's sensitivity, and has the advantages of simple preparation, convenient operation, and strong controllability. Experiments have shown that the optimal working temperature of the sensitive material prepared by the present invention is 60°C. Compared with traditional tin dioxide hydrogen-sensitive materials, the working temperature is significantly reduced, which is more in line with the requirements of practical applications. It can be seen that the preparation method of the present invention solves the technical problems of existing hydrogen-sensitive materials that are prone to safety accidents due to excessively high working temperatures, high costs due to the use of precious metal raw materials, and low sensitivity.

[0022] Furthermore, the cobalt ion concentration in the cobalt source solution is controlled at (0.5-6.0) mmol·L -1 The concentration of tin ions in the tin source solution is controlled at (0.5-5.0) mmol·L -1 , not only realizes the CoO xThe regulation of composition is also beneficial to the x The molar ratio of SnO2 is controlled at 1:(0.2~5.0).

[0023] Furthermore, the urea reagent is added at a mass percentage concentration of 0.1%-4.5%. First, it helps to evenly disperse the cobalt source and tin source in the precursor solution to form more uniform precursor particles. Uniform particle distribution is conducive to the formation of cobalt oxides with different oxidation states (such as CoO, Co2O3, Co3O4) during the heat treatment process and control their composition ratio; secondly, it is conducive to regulating the element valence and oxygen defect distribution of cobalt oxides with different oxidation states in sensitive materials, thereby adjusting the sensitivity of the material. Because NH3 and CO2 produced by the decomposition of urea at high temperature will be released during the heat treatment process, it helps to form pores and channels in the material. These pores and channels not only increase the specific surface area of ​​the material, but also facilitate the diffusion and adsorption of gas molecules, making hydrogen molecules more easily adsorbed and dissociated on the surface of the material, thereby improving the sensitivity of the material. At the same time, the formation of pores will also lead to an increase in oxygen defects in the material, which helps to promote the reaction of gas molecules and the electron exchange process on the surface of the material, thereby improving the hydrogen sensitivity of the material.

[0024] In the hydrogen-sensitive material prepared by the above preparation method, the p-type semiconductor cobalt oxide compound (CoO x ) contains variable-valence metal cobalt ions, oxygen ions, and oxygen defects, which are conducive to the active adsorption of gases or catalysis of subsequent gas-sensitive reactions. x It is considered to be a good gas-sensitive catalytic material. x The composite heterojunction can improve the chemical properties of the material interface, adjust the energy band structure, promote the adsorption of the target gas, and accelerate the chemical reaction. This heterostructure is conducive to showing a stronger hydrogen sensitive response at a lower operating temperature, as well as a faster response / recovery speed. Experiments show that the sensitivity of the hydrogen sensitive material of the present invention to 500ppm formaldehyde reaches 29. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 CoO prepared in Examples 1-5 of the present invention x / XRD pattern of SnO2 material;

[0026] Figure 2 CoO prepared in Examples 1-5 of the present invention x / Concentration-response relationship diagram of SnO2 material to 100-500ppm hydrogen;

[0027] Figure 3 CoO prepared in Examples 1-5 of the present invention x / Working temperature diagram of SnO2 material to 500ppmH2;

[0028] Figure 4 CoO prepared in Examples 1-4 of the present invention x / SEM image of SnO2 material. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] Example 1

[0033] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=0.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 10, and stir evenly to obtain a mixed solution A;

[0034] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:2 to make the cobalt ion concentration in the solution reach 1.0mmol·L -1 , recorded as solution B;

[0035] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:0.5 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 0.5%, and the resulting reaction system is precursor solution C;

[0036] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 200 W, and the treatment time is 2 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0037] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 450°C at a rate of 5°C / min, keep it warm for 5 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it in the furnace to obtain the target product.

[0038] Example 2

[0039] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 12, and stir evenly to obtain a mixed solution A;

[0040] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:1, so that the cobalt ion concentration in the solution reaches 3.0mmol·L -1 , recorded as solution B;

[0041] Step 3: Slowly drop solution B into solution A, and mix them in a molar ratio of 1:3 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 0.1%, and the resulting reaction system is precursor solution C;

[0042] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 50W, and the treatment time is 4 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0043] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 300°C at a rate of 15°C / min, keep it warm for 2h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0044] Example 3

[0045] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=3.0mmol·L -1, stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 9, and stir evenly to obtain a mixed solution A;

[0046] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:2 to make the cobalt ion concentration in the solution reach 3.0mmol·L -1 , recorded as solution B;

[0047] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:1.5 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 3.5%, and the resulting reaction system is precursor solution C;

[0048] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 150W, and the treatment time is 2h. The solution is placed at room temperature and aged for 12h, then fully dried in an oven at 60°C and ground into powder.

[0049] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 400°C at a rate of 2°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0050] Example 4

[0051] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0052] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.5 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0053] Step 3: Slowly drop solution B into solution A, mix them in a molar ratio of 1:4.0 to obtain a mixed solution, and then add a urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is a precursor solution C;

[0054] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 1.5 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0055] Step 5: Heat treatment process: put the obtained powder into a muffle furnace, heat it to 500°C at a rate of 5°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0056] Example 5

[0057] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=2.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 8, and stir evenly to obtain a mixed solution A;

[0058] Step 2: Dissolve pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water in a molar ratio of 1:2, so that the cobalt ion concentration in the solution reaches 2.0mmol·L -1 , recorded as solution B;

[0059] Step 3: Slowly drop solution B into solution A, mix them in a molar ratio of 1:1 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 3.0%, and the resulting reaction system is precursor solution C;

[0060] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 200 W, and the treatment time is 4 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0061] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 500°C at a rate of 10°C / min, keep it warm for 5h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0062] Example 6

[0063] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=2.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 8, and stir evenly to obtain a mixed solution A;

[0064] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water in a molar ratio of 1:4, so that the cobalt ion concentration in the solution reaches 2.0mmol·L -1 , recorded as solution B;

[0065] Step 3: Slowly drop solution B into solution A, mix them in a molar ratio of 1:1 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 3.0%, and the resulting reaction system is precursor solution C;

[0066] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 200 W, and the treatment time is 4 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0067] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 500°C at a rate of 10°C / min, keep it warm for 5h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0068] Example 7

[0069] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=0.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 10, and stir evenly to obtain a mixed solution A;

[0070] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:2 to make the cobalt ion concentration in the solution reach 0.5mmol·L -1 , recorded as solution B;

[0071] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:0.5 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 0.5%, and the resulting reaction system is precursor solution C;

[0072] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 200 W, and the treatment time is 2 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0073] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 450°C at a rate of 5°C / min, keep it warm for 5 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it in the furnace to obtain the target product.

[0074] Example 8

[0075] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L-1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 12, and stir evenly to obtain a mixed solution A;

[0076] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:1, so that the cobalt ion concentration in the solution reaches 6.0mmol·L -1 , recorded as solution B;

[0077] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:3 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 0.1%, and the resulting reaction system is precursor solution C;

[0078] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 50W, and the treatment time is 4 hours. The solution is placed at room temperature and aged for 12 hours, then fully dried in an oven at 60°C and ground into powder.

[0079] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 300°C at a rate of 15°C / min, keep it warm for 2h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0080] Example 9

[0081] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=5.0mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 9, and stir evenly to obtain a mixed solution A;

[0082] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:2 to make the cobalt ion concentration in the solution reach 3.0mmol·L -1 , recorded as solution B;

[0083] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:1.5 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 3.5%, and the resulting reaction system is precursor solution C;

[0084] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 150W, and the treatment time is 2h. The solution is placed at room temperature and aged for 12h, then fully dried in an oven at 60°C and ground into powder.

[0085] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 400°C at a rate of 2°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0086] Example 10

[0087] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0088] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.5 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0089] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0090] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0091] Step 5: Heat treatment process: put the obtained powder into a muffle furnace, heat it to 500°C at a rate of 5°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0092] Embodiment 11

[0093] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0094] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.5 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0095] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0096] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0097] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 500°C at a rate of 20°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0098] Example 12

[0099] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0100] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.5 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0101] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0102] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0103] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 4 hours, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0104] Embodiment 13

[0105] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L-1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0106] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.5 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0107] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0108] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0109] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 1h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0110] Embodiment 14

[0111] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0112] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:0.2 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0113] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0114] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0115] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 1h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0116] Embodiment 15

[0117] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0118] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:5.0 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0119] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:4.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0120] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0121] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 1h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0122] Example 16

[0123] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0124] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water with a molar ratio of 1:5.0 to make the cobalt ion concentration in the solution reach 2.0mmol·L -1 , recorded as solution B;

[0125] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:0.2 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0126] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0127] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 1h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0128] Embodiment 17

[0129] Step 1: Dissolve analytical pure SnCl2·2H2O in deionized water to control [Sn 2+ ]=1.5mmol·L -1 , stir magnetically until completely dissolved, then add sodium hydroxide, adjust the pH value to 7, and stir evenly to obtain a mixed solution A;

[0130] Step 2: Dissolve analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water at a molar ratio of 1:5.0, so that the cobalt ion concentration in the solution reaches 2.0mmol·L -1 , recorded as solution B;

[0131] Step 3: Slowly drop solution B into solution A, and mix them at a molar ratio of 1:5.0 to form a mixed solution, and then add urea reagent, the mass fraction of which in the mixed solution is 4.5%, and the resulting reaction system is precursor solution C;

[0132] Step 4: The precursor solution is first subjected to ultraviolet ultrasonic treatment, the ultraviolet lamp is a mercury lamp, the ultrasonic power is 300 W, and the treatment time is 0.5 h. The solution is placed at room temperature and aged for 12 h, then fully dried in an oven at 60° C. and ground into powder.

[0133] Step 5 heat treatment process: put the obtained powder into a muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 1h, then cool it to 100°C at a rate of 10°C / min, and finally cool it with the furnace to obtain the target product.

[0134] Figure 1 The CoO prepared in Example 1-4 x The XRD diagram of the SnO2 hydrogen-sensitive material shows that the main crystalline phase of the material prepared by the process designed by the present invention is SnO2, At the same time, the material also contains a certain amount of Co3O4 or CoO.

[0135] Figure 2 CoO prepared by different embodiments x / The response diagram of SnO2 material to 100-500ppm hydrogen. It can be seen from the figure that the concentration-response of the material conforms to the linear growth law, among which the material prepared in Example 4 has the best sensitivity, and the sensitivity to 500ppm formaldehyde reaches 29.

[0136] Figure 3 CoO prepared by different embodiments x / SnO2 material working temperature diagram, from which it can be seen that the optimal working temperature of the sensitive material prepared by the present invention is 60°C. Compared with the traditional tin dioxide hydrogen sensitive material, the working temperature is significantly lower, which is more in line with the requirements of practical applications.

[0137] Figure 4 CoO prepared by using different amounts of urea in Examples 1-4 of the present invention x / SnO2 material SEM picture, through experimental measurement, CoO x / SnO2 hydrogen-sensitive material has an average particle size of 10-50nm, presents a polyhedral morphology and is evenly distributed.

[0138] In summary, the present invention mixes stannous chloride, cobalt chloride and cobalt nitrate to prepare a solution, adds sodium hydroxide and urea to adjust the degree of reaction, and accurately controls the raw material ratio, urea addition amount, ultraviolet ultrasonic power and heat treatment system to obtain CoO with controllable composition and morphology. x / SnO2 hydrogen-sensitive material. By constructing a heterostructure and introducing CoO x As a catalyst, it can effectively improve the sensitivity and activity of materials and reduce the working temperature.

[0139] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A CoO x / SnO2 hydrogen sensitive material preparation method, characterized in that, The following steps are involved: 1) Cobalt source solution and Sn-containing 2+ The alkaline aqueous solution is fully mixed to form a mixed solution, wherein the cobalt source and Sn 2+ The molar ratio is 1:(0.2-5.0); 2) adding urea reagent to the mixed solution to obtain a precursor solution; 3) subjecting the precursor solution to ultraviolet ultrasonic treatment, aging, drying and grinding to obtain powder; 4) Heat treat the powder to obtain the target product CoO x / SnO2 hydrogen sensitive material.

2. A CoO according to claim 1 x / SnO2 hydrogen sensitive material preparation method, characterized in that, In step 1), the cobalt source solution is prepared by dissolving analytically pure Co(NO3)2·6H2O and CoCl2·6H2O in deionized water at a molar ratio of 1:(0.2-5.0).

3. A CoO according to claim 2 x / SnO2 hydrogen sensitive material preparation method, characterized in that, The cobalt ion concentration in the cobalt source solution reaches (0.5-6.0) mmol·L -1 .

4. A CoO according to claim 1 x / SnO2 hydrogen sensitive material preparation method, characterized in that, In step 1), Sn 2+ The alkaline aqueous solution is prepared by dissolving analytically pure SnCl2·2H2O in deionized water and stirring, then adding sodium hydroxide and adjusting the pH value to 7-12.

5. A CoO according to claim 4 x / SnO2 hydrogen sensitive material preparation method, characterized in that, Contains Sn 2+ The concentration of tin ions in the alkaline aqueous solution reaches (0.5-5.0) mmol·L -1 .

6. A CoO according to claim 1 x / SnO2 hydrogen sensitive material preparation method, characterized in that, In step 2), the mass fraction of the urea reagent in the mixed solution is 0.1%-4.5%.

7. A CoO according to claim 1 x / SnO2 hydrogen sensitive material preparation method, characterized in that, In step 3), the ultraviolet ultrasonic treatment uses a mercury lamp, the ultrasonic power is 50W-300W, and the treatment time is 0.5h-4h; after the ultraviolet ultrasonic treatment, the precursor solution needs to be aged at room temperature for 12h and placed in a 60°C oven to be fully dried.

8. A CoO according to claim 1 x / SnO2 hydrogen sensitive material preparation method, characterized in that, In step 4), the heat treatment process is as follows: the obtained powder is placed in a muffle furnace, the temperature is increased to 300°C-600°C at a rate of 2°C / min-20°C / min, and the temperature is kept for 1h-5h, then the temperature is decreased to 100°C at a rate of 10°C / min, and finally the target product is obtained by cooling with the furnace.

9. A CoO according to any one of claims 1 to 8 x CoO / SnO2 hydrogen sensitive material preparation method x / SnO2 hydrogen sensitive material, characterized in that The hydrogen-sensitive material has a heterogeneous structure.

10. CoO according to claim 9 x / Application of SnO2 hydrogen sensitive materials in hydrogen detection.

Citation Information

Patent Citations

  • Tin oxide-based hydrogen sensing material based on rare earth element doping and precious metal modification as well as preparation method and application of tin oxide-based hydrogen sensing material

    CN114609198A